Virtual Women Philanthropy: A Portrait of the Women's Generosity Movement for the Rahim and Janin Community on Social Media During the Pandemic - Khoniq Nur Afiah (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2022)
This article examines the movement of women's generosity during the COVID-19 pandemic on social media. These movements were born purely from women's awareness of the welfare of society, especially women. Women as one of the vulnerable groups whose welfare is considered, even though the conditions in the field they work hand in hand to solve the problems women are facing. During the pandemic, women whose public work is hampered, they cooperate in creating informal jobs such as making masks, hand sanitizer, and so on. This research will focus on several movements or communities that are actively engaged in social media such as Instagram in carrying out generosity movements. The community that is the object of research is Rahim Janin. The Rahim and Fetal Community has a massive movement in providing services or generosity movements for women during the COVID-19 pandemic. The research method in this study is a qualitative-descriptive and virtual ethnographic approach, then the data obtained is analyzed with the help of an analysis knife of the concept of philanthropy and the concept of women in the world of philanthropy. Two sources of data in this study are primary data from interviews and secondary data from observations of the generosity movement carried out by the Rahim Janin community on social media. The results of this study indicate that women's virtual philanthropy movements in social media can be categorized into two types of philanthropy, namely charitable forms and forms of empowerment. The charitable form is in the form of raising funds for women, where the funds can be applied in the form of assistance in the form of educational scholarships, then there is also online counseling for vulnerable women during the COVID-19 pandemic. Meanwhile, philanthropy movements that fall into the empowerment category are education on unplanned pregnancies during the pandemic, scholarships for friends, and education about maternal mental health during the pandemic.